Clinical significance of prognostic nutritional index in renal cell carcinomas. Issue 10 (12th March 2021) - Tang, Yongquan; Liang, Jiayu; Liu, Zhihong; Zhang, Ruochen; Zou, Zijun; Wu, Kan; Lu, Yiping; Wei, Xin
Abstract : Abstract: Prognostic nutritional index (PNI) could reflect the nutrition and inflammation status in cancer patients. This study aims to identify the prognostic significance of PNI in patients with renal cell carcinoma (RCC). A total of 694 RCC patients from our institution were included in this study. The prognostic correlation between PNI and overall survival (OS) and recurrence-free survival (RFS) was analyzed respectively using Kaplan–Meier method and univariate and multivariate Cox model. Studies about the association between pretreatment or preoperative PNI and prognosis of RCC were systemically reviewed and a meta-analysis method was performed to further evaluate the pooled prognostic value of PNI in RCC. 267 (38.47%) RCC patients had low PNI according to the cut off value (49.08). Low PNI was associated with poor OS ( P  < .001) and RFS ( P  < .001), respectively. In the multivariate Cox analysis, PNI was identified to be an independent prognostic factor for OS (hazard ratio [HR] = 2.13, 95%CI: 1.25–3.62, P  = .005). Compared to other nutritional indexes, this risk correlation of PNI is better than that of geriatric nutritional risk index (GNRI; HR = 1.19; P  = .531), while is no better than that of neutrophil–lymphocyte ratio (NLR; 1/HR = 2.56; P  < .001) and platelet–lymphocyte ratio (PLR; 1/HR = 2.85; P  < .001) respectively. Meanwhile, additional 4785 patients from 6 studies were included into pooled analysis. For RCC patients who underwent surgery, low preoperative PNI was significantly associated with worse OS (pooled HR = 1.57, 95%CI: 1.37–1.80, P  < .001) and worse RFS (pooled HR = 1.69, 95%CI: 1.45–1.96, P  < .001). Furthermore, low PNI (<41–51) was also significantly associated with poor OS (HR = 1.78, 95%CI: 1.26–2.53 P  < .05) and poor RFS (HR = 2.03, 95%CI: 1.40–2.95, P  < .05) in advanced cases treated with targeted therapies. The present evidences show that PNI is an independent prognostic factor in RCC. Low PNI is significant associated with poor prognosis of RCC patients.